Effect of dietary supplementation of Eclitpa alba on oxidative stress and liver damage induced by aflatoxin in broilers - UMAYA, R S; MANPAL, S; KRISHNAMOORTHY, P; SEJIAN, V; DAVID, I C G (The Indian Journal of Animal Sciences, 2018)
The primary aim of the present study was to evaluate the efficacy of Eclipta alba leaf powder to ameliorate the oxidative stress and liver damage induced by aflatoxin B1 (AFB1) in broilers. Day-old male broilers were fed with basal diet (control), basal diet supplemented with E. alba (1.0%), basal diet with 1.0 ppm AFB1 or AFB1 (1.0 ppm) with E. alba (1.0%) for 42 days. Birds fed AFB1 showed significantly higher serum AST and ALT activities, and decreased concentrations of total protein, cholesterol and albumin. AFB1 feeding significantly increased hepatic lipid peroxidation products, decreased antioxidant enzymes and induced pathological changes in liver. The supplementation of E. alba leaf powder with AFB1 contaminated diet significantly improved serum biochemical profile, reduced the oxidative stress and pathological changes in liver. The present study revealed that supplementation of E. alba reduces the liver damage and oxidative stress induced by AFB1 and offer protection against aflatoxin toxicity in broilers.